دور التحول الرقمي في تفعيل التعليم الإلكتروني في جامعة الملك خالد خلال جائحة كورونا (19-COVID) - عبدالخير، آسيا يعقوب الهادي (المركز القومي للبحوث غزة, 2021)
هدف البحث إلى الوقوف على الدور الهام الذي يلعبه التحول الرقمي في تفعيل وتطوير التعليم الإلكتروني إذ أحدث التحول الرقمي تغيرا جذريا في كافة المجالات وخاصة في مجال التعليم إذ سمح بظهور طرق وأساليب تعليمية حديثة واستخدام الوسائل والبرامج التكنولوجية، من اهم المؤسسات التي حرصت على تبني وتطبيق مفهوم التحول الرقمي هي مؤسسات التعليم العالي إذ يسهم تطبيقه في خفض التكلفة التشغيلية للمؤسسات واستحداث وسائل تعليمية حديثة تعتمد على التفاعل والتشارك وعلى تنوع الوسائل والوسائط التعليمية. مع التطور السريع في عالم التقنية واتجاه الحكومات والمؤسسات نحو الرقمية في كافة خدماتها من خلال تقديمها لخدمات رقمية بطريقة سلسة وسهلة توفر الجهد والوقت والمال على المستفيدين، في عصرنا الحالي حرصت كل المؤسسات على تبني مفهوم التحول الرقمي باستبدال العمليات الرقمية بالتقليدية، ووضع خطط واستراتيجيات لضمان تحقيق أهدافها بجودة وكفاءة فالتحول الرقمي قادر على خلق بيئة تنافسية تقنية جاذبة تحقق أعلى مستويات الجودة بأقل التكاليف، هذا وإن انتشار واستخدام كل ما هو رقمي قد تسارع على مدى الأعوام العشر الماضية. فرضت عدة تحديات على التعليم التقليدي خاصة خلال جائحة كورونا (كوفيد-19) الذي يجعل من الاعتماد على الوسائل التعليمية التقليدية أمرا صعبا لذا جاء البحث بهدف التعرف على دور التحول الرقمي (التعلم الرقمي) بجامعة الملك خالد على تطوير وفعالية التعلم الإلكتروني في ظل الجائحة، اتبعت الورقة المنهج الاستقرائي والمنهج الكيفي، تم استخدام الملاحظة، التقارير، المعلومات الوثائقية والمواقع الإلكترونية لجامعة الملك خالد لجمع البيانات. تم التطرق لمفاهيم التحول الرقمي وكذلك التعليم الإلكتروني ومن ثم تم التوصل لمجموعة من النتائج منها أن جامعة الملك خالد تمتاز بوجود نظام إلكتروني فعال، أن البيئة التقنية لتكنولوجيا المعلومات قد مكنت جامعة الملك خالد من مواجهه التغير السريع في بيئة العمل وخلص البحث لبعض التوصيات. منها أن التحول الرقمي لم يعد خيارا، بل أصبح ضرورة لذا لابد من مواكبة التطورات التقنية والاستفادة منها في التحول نحو التعلم الرقمي. The study aimed to identify the important role that digital transformation plays in activating and developing e-learning, as digital transformation has radically changed in all fields, especially in the field of education, as it allowed the emergence of modern educational methods and methods. With the rapid development in the world of technology and the trend of governments and institutions towards digital in all their services by providing digital services in a smooth and easy way that saves effort, time and money for the beneficiaries, in our current era all institutions have been keen to adopt the concept of digital transformation by replacing traditional digital processes, and developing plans and strategies to ensure the achievement of Its objectives are of quality and efficiency, as the digital transformation is able to create a competitive and attractive technical environment that achieves the highest levels of quality at the lowest costs, and that the spread and use of everything digital has accelerated over the past ten years Several challenges have imposed on traditional education, especially in light of the Corona pandemic (Covid-19), which makes relying on traditional educational methods difficult, so the study came with the aim of identifying the role of digital transformation (digital learning) at King Khalid University on the development and effectiveness of e-learning in light of the pandemic The paper followed the inductive approach and the qualitative approach. Observation, reports, documentary information and King Khalid University websites were used to collect data. The concepts of digital transformation as well as e-learning were addressed, and then a set of results were reached. King Khalid University is distinguished by the existence of an effective electronic system, that the technical environment for information technology has enabled King Khalid University to face the rapid change in the work environment, and the study concluded some recommendations. One of them is that digital transformation is no longer an option, rather it has become a necessity, so it is necessary to keep pace with technological developments and to benefit from them in the transformation towards digital learning.
Keywords: التقنيات الرقمية -- التعليم الإلكتروني -- الجامعات السعودية -- فيروس كورونا "كوفيد-19"